Shattering dawn [large type] - Krentz, Jayne Ann (Krentz, Jayne Ann. Lost night files, 2025)
Amelia Rivers, a member of the Lost Night Files podcast team, hires private investigator Gideon Sweetwater to catch the stalker who has been watching her. Amelia suspects the stalker may be connected to the shadowy organisation responsible for the night that she and her two friends lost to amnesia - a night that upended their lives and left them with paranormal talents. Gideon suspects that Amelia is either paranoid or an outright con artist, but he can't resist the chemistry between them. For her part, Amelia has second thoughts about the wisdom of employing the mysterious Mr Sweetwater. She knows she doesn't have time to find another investigator, and Gideon is forced to reckon with the truth when he disrupts what was intended to be Amelia's kidnapping. Now the pair is on the run, with no choice but to return to the haunting ruins of the old hotel where Amelia's lost night occurred. They are desperate to stop a killer and the people who are conducting illegal experiments with a dangerous drug that is designed to enhance psychic abilities. If they are to survive, they will have to trust each other and the passion that bonds them.